Conceptualizing Essential Components of Effective High Schools. Issue 4 (2nd October 2017) - Preston, Courtney; Goldring, Ellen; Guthrie, J. Edward; Ramsey, Russell; Huff, Jason
ABSTRACT: Three decades of reform aimed at improving disadvantaged student achievement have not substantially narrowed achievement and graduation gaps. This article reviews the research around eight essential components of effective high schools emerging from a review of the effective schools and high school reform literature, and provides a framework for how these components are implemented and integrated. We submit that far-reaching high school improvement is rooted in these components: schools succeed because they are woven into the school's organizational fabric to create internally consistent and mutually reinforcing reforms; their success is explained by more than the simple sum of their parts.